2019
DOI: 10.3390/ijms20133165
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Metabolomics Reveal the Mechanism Underlying the Anti-Atherosclerotic Effects of Aspirin Eugenol Ester on Vascular Endothelial Dysfunction

Abstract: Aspirin eugenol ester (AEE) possesses anti-thrombotic, anti-atherosclerotic and anti-oxidative effects. The study aims to clarify the mechanism underlying the anti-atherosclerotic effects of AEE on vascular endothelial dysfunction. Both the high-fat diet (HFD)-induced atherosclerotic rat model and the H2O2-induced human umbilical vein endothelial cells (HUVECs) model were used to investigate the effects of AEE on vascular endothelial dysfunction. UPLC/QTOF-MS coupled with a multivariate data analysis method we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Increased expression of VCAM-1 in HFD group showed a positive tendency. This result is accordance with previous research by Huang et al, reported that after treating rats with HFD for 12 weeks, VCAM-1 expression in the aorta and the levels of sVCAM-1 were increased significantly [23]. After EEMP administration, VCAM-1 expression displayed a significant decrease.…”
Section: Discussionsupporting
confidence: 93%
“…Increased expression of VCAM-1 in HFD group showed a positive tendency. This result is accordance with previous research by Huang et al, reported that after treating rats with HFD for 12 weeks, VCAM-1 expression in the aorta and the levels of sVCAM-1 were increased significantly [23]. After EEMP administration, VCAM-1 expression displayed a significant decrease.…”
Section: Discussionsupporting
confidence: 93%
“…However, the quantitative measurement of exometabolites in supernatants after cell culture, and comparison to control media not put in contact with cells, allows the determination of consumption and secretion rates per unit of time that convey rich insights over cellular metabolism. Indeed, exometabolites rates are excellent reporters of the cell physiology that allow for the predicting of the intracellular metabolic state and evidence mechanisms of chemical-induced metabolic reprogramming [ 20 , 144 ]. For example, glucose consumption and lactate/pyruvate secretion rates are simple to determine yet powerful indicators of the glycolytic activity in cells [ 47 ], and the extracellular secretion of citrate and succinate evidence mitochondrial metabolism remodeling.…”
Section: Addressing Cellular Response To Xenobioticsmentioning
confidence: 99%
“…Metabolic modeling exploits multiple facets of metabolomics approaches for the characterization of whole organisms, their pathologies, and adaptations to changeable environmental conditions. Metabolomic analyses of body fluids refer to systemic overviews of an organism’s state, however concealing important information about the behavior of cells that underlie changes in the dynamic homeostasis at the organism level [ 9 , 20 ]. Modeling cellular metabolism allows one to investigate biological processes but also serves a predictive role for verifying diagnostic hypotheses using cell cultures in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new compound, AEE plays an active role in many aspects [31][32][33][34][35][36][37][38][39][40]. AEE can prevent tail thrombosis induced by kappa-carrageenan in rats [39].…”
Section: Introductionmentioning
confidence: 99%